RFID tag deployment optimization scheme for indoor navigation for the visually impaired persons - Wong, Siew Mooi (Universiti Malaysia Sarawak (UNIMAS), 2013)
Navigation from one place to another place is a common task in our daily life. Global Positioning System (GPS) is one of the most developed technologies for outdoor navigation. However, GPS is not recommended for indoor navigation due to its low accuracy in providing location information at indoor spaces. As the replacement, Radio Frequency Identification (RFID) technology gives excellent accuracy in estimating location indoor environment. As to date, more buildings are getting more complex such as government agencies, college and campuses, or shopping mall. However they are seldom equipped with indoor navigation facilities which are useful for the visually impaired (VI). In order to create an indoor environment which is friendly for indoor navigation of the VI, normally large quantities of tags are needed to be deployed all over the building. However, deployment of indoor navigation system inside of a building is not an easy task especially for large scale or multistoried buildings. Implementation and deployment limitations such as inefficient in planning the path for placing the tags and also estimating the quantity of tag required have been issues to the technology implementers. In order to increase the deployment rate of a RFID-based network for VI-centered indoor navigation system, the deployment process of such network need to be shortened. Time and cost effectiveness of the deployment process of this network can be achieved if the limitations mentioned above can be addressed. Hence, this research focuses on proposing an efficient RFID Tag Deployment Optimization Scheme for VI-centered indoor navigation system which can automatically plan optimal paths for the VI-centered indoor navigation network. The proposed scheme also can estimate the number of RFID tag required for the optimal paths in the building based on the standard tag placement guidelines adopted. Such Tag Deployment Optimization Scheme adopted the Shortest Path Approach v and Optimization Approach in order to generate the optimal network of path which has lower path cost. In this research, the Shortest Path Approach gives 22% reduction in the path cost which is apparently lower than the path cost obtained from the path of the Conventional Tag Deployment Method. After the Shortest Path Approach was enhanced by the Optimization Approach, there is 14% decrease in path cost generated by the Shortest Path Approach. When compared to the Conventional Tag Deployment Method, there is a 33% reduction, which has shown that Optimization Approach has much more influence in reducing the path cost for the same floor plan.